2013
DOI: 10.1152/ajpendo.00254.2013
|View full text |Cite
|
Sign up to set email alerts
|

p-FAK-Tyr397 regulates spermatid adhesion in the rat testis via its effects on F-actin organization at the ectoplasmic specialization

Abstract: Wan HT, Mruk DD, Li SY, Mok KW, Lee WM, Wong CK, Cheng CY. p-FAK-Tyr 397 regulates spermatid adhesion in the rat testis via its effects on F-actin organization at the ectoplasmic specialization. Am J Physiol Endocrinol Metab 305: E687-E699, 2013. First published July 23, 2013; doi:10.1152/ajpendo.00254.2013.-During spermatogenesis, the molecular mechanism that confers spermatid adhesion to the Sertoli cell at the apical ectoplasmic specialization (apical ES), a testis-specific F-actin-rich adherens junction, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 40 publications
5
53
0
Order By: Relevance
“…This in vitro system is widely used by investigators to study BTB dynamics (Janecki et al, 1992;Lie et al, 2012;Nicholls et al, 2009;Qiu et al, 2013). Furthermore, findings obtained by using this in vitro system have been reproduced in studies in vivo (Lui et al, 2003;Qiu et al, 2013;Su et al, 2012;Wan et al, 2013), illustrating its physiological relevance. As such, the effect of p-rpS6 on the Sertoli cell tight junction barrier was first investigated by quantifying changes in the tight junction permeability across the Sertoli cell epithelium following the overexpression of different constructs.…”
Section: Resultsmentioning
confidence: 83%
“…This in vitro system is widely used by investigators to study BTB dynamics (Janecki et al, 1992;Lie et al, 2012;Nicholls et al, 2009;Qiu et al, 2013). Furthermore, findings obtained by using this in vitro system have been reproduced in studies in vivo (Lui et al, 2003;Qiu et al, 2013;Su et al, 2012;Wan et al, 2013), illustrating its physiological relevance. As such, the effect of p-rpS6 on the Sertoli cell tight junction barrier was first investigated by quantifying changes in the tight junction permeability across the Sertoli cell epithelium following the overexpression of different constructs.…”
Section: Resultsmentioning
confidence: 83%
“…In short, toxicants induce restructuring of the apical ES in early and elongating spermatids by disrupting the actin microfilament organization, pushing immature spermatids to undergo ‘spermiation’; toxicants also induce similar changes at the basal ES/BTB, forcing the BTB to enter a stage VIII-like restructuring, reversing the timely events of the epithelial cycle (Figure 2). These changes in the localization of actin regulatory proteins following toxicant-induced germ cell defoliation from the testis may be regulated, at least in part, by FAK, in particular p-FAK-Tyr 407 and p-FAK-Tyr 397 , based on recent studies [56,100]. For instance, p-FAK-Tyr 397 is known to confer apical ES integrity and its presence is detected at the apical ES until spermiation at late stage VIII [56,101,102].…”
Section: Molecular Models By Which Environmental Toxicants Perturbmentioning
confidence: 99%
“…Studies in vitro (Lie, et al 2012) and in vivo (Wan, et al 2013) based on the use of phosphomimetic vs. non-phosphorylatable mutants have shown that the two phosphorylated (activated) forms of FAK, namely p-FAK-Tyr 407 and p-FAK-Tyr 397 , are crucial regulators of ES including the basal ES/BTB and the apical ES in the rat testis (for reviews, see (Wan, et al 2014, Xiao, et al 2014b)). For instance, p-FAK-Tyr 407 is highly expressed at the basal ES/BTB in the testis based on studies using dual-labeled immunofluorescence analysis and confocal microscopy (Lie, et al 2012).…”
Section: Regulation Of Btb Actin-based Cytoskeleton By Abps and Prmentioning
confidence: 99%